Examining Recall of the House Member: How Does It Impact on Eradicating Corruption in Indonesia? - Jayus Jayus; Muhammad Bahrul Ulum; Moch. Marsa Taufiqurrohman (Lentera Hukum, 2020)
This study aims to discuss the existing contentious recall policy that becomes the legitimate reason to replace or retire the House member proposed by political parties. The discussion also examines to what extent recall, in practice, whether it enables the promotion of Indonesia's anti-corruption agenda. Through the recall, political parties can withdraw their members in the House, either in the form of dismissal or changing positions before the end of the term of office of members who sit in the House of representatives. This study finds that the existing recall policy impedes democracy and negates how to eradicate corruption in Indonesia. As a result, the current policy needs an option to ensure that recall will work as it is expected. Therefore, this alternative should include constituents to propose recall, which will disrupt the existing parties' domination, resulted in a more participatory system, and it reflects the more reciprocal ways to link people, parties, and the House in Indonesian politics. The judiciary's role is another essential aspect to highlight, in which the process and settlement of the recall may involve the Constitutional Court as the hub of the political and constitutional settlement. KEYWORDS: Indonesian Democracy, Anti-Corruption Agenda, Recall Policy, Political System.